PENGARUH CURRENT RATIO (CR), DEBT TO EQUITY RATIO (DER), RETURN ON ASSET (ROA), DAN TOTAL ASSET TURNOVER(TATO) TERHADAP PERTUMBUHAN LABA PADAPERUSAHAANSUB SEKTOR MAKANAN DANMINUMAN YANG TERCATAT DIBEI PERIODE 2012-2016 - Nicia Lestari; Jesselin Chandra; Venessa ,; Darwin . (JRAM (Jurnal Riset Akuntansi Multiparadigma), 2019)
Food and beverage companies are sub sectors of the consumer goods industry. From year to year the number of population in the country of Indonesia is increasing and as the increase will be greater also the level of public consumption. This research aims to determine the influence of current ratio, debt to equity ratio, return on asset, and total asset turnover on the growth of the food and beverage sub-sector company recorded in IDX period 2012-2016. This research uses secondary data with a method of documentation analysis which is the company's annual financial report from 2012-2016. The approach used in research is a quantitative approach with purposive sampling methods. Out of a total of 16 companies, only 12 companies meet the criteria to be sampled. The data analysis technique used is multiple linear regression. The results showed that a partial current ratio and debt to equity ratio were negatively and insignificant in profit growth, and the total asset turnover was positively and significantly influential on profit growth while Return on asset has no effect on profit growth. Simultaneously current ratio, debt to equity ratio, return on asset, and total asset turnover have significant effect on the growth of profit in the food and beverage sub-sector company recorded in IDX period 2012-2016.